AN OVERVIEW OF THE REGULATION OF CRYPTOCURRENCY IN SOUTH AFRICA (The Pretoria Student Law Review, 2021)
The increasing popularity of cryptocurrencies has raised many questions with regard to their regulation. Issues such as taxation and its role in criminal activities are of central importance to the way in which cryptocurrency will continue to develop and occupy space in society. In this paper, such regulatory aspects are explored, and South Africa’s response is addressed. With cryptocurrency growing worldwide at increasing rates, regulators are left having to respond quickly to this aspect of financial technology and while some have banned its use outright, others have taken the stance to embrace the use of cryptocurrencies to ensure it has a space for use in the future of the financial world.
Keywords: financial technology; cryptocurrency; cybercrimes; regulation